Effects of a proton pump inhibitor on laryngeal irritation in patients with laryngopharyngeal reflux - Külekçi, Mehmet; Budun, Rıdvan; Özgür Avinçsal, Mehmet; Dizdar, Denizhan; Ulusoy, Seçkin; Necati Develioğlu, Ömer; Topak, Murat (ENT Updates, 2015)
Objective: To evaluate laryngeal irritation before and after treatment using the reflux symptom index (RSI) in patients diagnosed with laryngopharyngeal reflux (LFR). Methods: A total of 30 patients who were diagnosed with LFR after 24 hours of dual-probe pH monitoring were included in the study. RSI was applied to the patients before and after treatment. In evaluating the patients’ symptoms, throat clearing need and post-nasal drainage, which are frequently observed in LFR, were evaluated post-treatment. The patients were followed for 3 months during proton pump inhibitor treatment. Data regarding the patients’ LFR symptoms were obtained after 3 months, and the responses to treatment based on reflux symptom scale scores, post-nasal drainage, and throat clearing need were evaluated and compared with those pre-treatment. Results: The decrease in the RSI for postnasal drainage value was statistically significant after treatment. The decrease in the throat clearing RSI value was statistically significant after treatment. Conclusion: In patients with persistent postnasal drainage and throat clearing need complaints, if no infection source is identified, the patients should be evaluated by 24-hour pH monitorization in terms of LFR, irrespective of the presence or absence of laryngoscopic findings.